Chemistry of Antibiotics and Related Drugs - Bhattacharjee, Mrinal K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This textbook discusses how the various types of antibiotics and related drugs work to cure infections. It also delves into the very serious matter of how bacteria are becoming resistant to antibiotics. Appropriate for a one-semester course at either the graduate or advanced undergraduate level, this textbook contains worked examples of experimental procedures and methods of interpreting data.
Introduction -- Antibiotic resistance development -- Major classes of antibiotics -- Relevant concepts in Biochemistry -- The cell wall as a target -- Mechanism of resistance to B-lactams -- Antibiotic Vancomycin -- Antibiotics that inhibit nucleotide synthesis -- Antibiotics that inhibit DNA synthesis -- Drugs that cause DNA cleavage -- Antibiotics that inhibit RNA synthesis -- Antibiotics that inhibit RNA synthesis -- Antibiotics that disrupt membrane structure.
Keywords: Medicinal chemistry; Clinical biochemistry; Microbiology; Pharmacy; Pharmacology; Medicinal Chemistry; Medical Biochemistry; Microbiology; Pharmacy; Pharmacology